THE USE OF SONGS IN TEACHING STUDENTS' LISTENING ABILITY : A Quasi Experimental Study of the Second Grade Students of a Junior High School in Sumedang - Hidayat, Apin (2012)
This study entitled "The Use of Songs in Teaching Students' Listening Ability" was aimed at first investigating whether or not the use of songs is significantly improves the students' listening skill. Second, the difficulties faced by the students in listening comprehension were also investigated. This quasi-experimental research involved two classes of students of a public junior high school in Sumedang. The data were collected through pretest, posttest and questionnaires. In analyzing the collected data, quantitative research method was employed. Furthermore, the data taken from questionnaires were also investigated to find out the difficulties faced by the students listening comprehensions through songs. The study found that the use of songs likely improves students' listening comprehension skills. It was evidenced by the result of independent t-test which revealed that the value of tobt (6.542) was greater than tcrit. As the result of the study, the null hypothesis of this research was rejected; the use of songs is likely to improve the students' listening comprehension skill.